Serological association between Leishmania infantum and sand fly fever Sicilian (but not Toscana) virus in sheltered dogs from southern Portugal - Maia, Carla (2018)
Background: Phlebotomine sand fly-borne diseases such as leishmanioses and phleboviruses are emerging threats to animal and public health. Canine leishmaniosis caused by Leishmania infantum is an endemic zoonosis in Portugal. Antibodies to Toscana virus (TOSV) and sand fly fever Sicilian virus (SFSV) were also reported in dogs from the south of the country. The aim of this work was to evaluate a possible association between exposure to L. infantum, TOSV and SFSV in sheltered dogs from the south of Portugal. Results: Seventy-six (13.1%) out of 581 dogs were seropositive for L. infantum, 327 (56.3%) for SFSV and 36 (6.2%) for TOSV. Six dogs were co-exposed with L. infantum and TOSV, 51 with L. infantum and SFSV and 25 with TOSV and SFSV. One dog had antibodies to the three pathogens. Leishmania infantum seroprevalence was significantly higher in pure breed dogs than in mongrels and in dogs with clinical signs while SFSV positivity was significantly higher in males, in pure and cross-breed dogs than in mongrels and in those not treated with insecticides. Seroprevalence for both viruses was significantly higher in dogs over than 7 years-old than in those aged 1-7. A significant association was observed between the presence of antibodies to L. infantum and SFSV. Conclusions: The presence of antibodies to several phlebotomine sand fly-borne pathogens in dogs, reinforces the need to implement efficient prophylactic measures to prevent infection among vertebrate hosts including humans. The results also indicate that dogs are good sentinels for assessing human exposure to TOSV and SFSV. Further studies must be performed to elucidate the role of dogs in the dynamics of transmission and if they can play a role as amplifying or reservoir hosts in the natural cycle of these viruses. Public and animal health impacts of these phleboviruses in Portugal should be addressed via serological and virological studies on both phlebotomine sand flies and vertebrate hosts, especially on humans.